Model Pemantau Kelembaban dan Irigasi Sawah Otomatis Berbasiskan Internet of Things - April Firman Daru; Whisnumurti Adhiwibowo; Alauddin Maulana Hirzan (Computer Engineering Departement, Universitas Komputer Indonesia, 2021)
Today's technological developments have a significant impact on the progress of human life. Apart from helping many sectors of human life, technology can also help agriculture. Unlike other fields, rice fields have strict requirements to ensure plants can grow well. Since the humidity level of the rice field will influence the harvest outcome, the consistency of the humidity in the medium must be well-maintained. The insufficient moisture in the rice field may inhibit plant growth in the rice field. The main challenge of irrigating rice fields is the manual irrigation process carried out by the farmer. This process requires more energy and time to water large areas. Therefore, this study aims to design a humidity monitoring and automatic irrigation model based on the Internet of Things to reduce the burden on farmers during irrigations. This model is equipped with a humidity sensor to monitor humidity and a mini water pump to drain water to control soil moisture. Besides that, this model is equipped with WiFi connectivity for monitoring the humidity level of their rice fields. From the model evaluation process, this model can stabilize soil moisture well. Hence, stable humidity can optimize plant growth in the rice fields.